Sandbury Lock (Draft 2) - Daugharty, Janice (My University, 1989)
Daugharty, Janice. "Sandbury Lock," 1989. Series 2: The Short Stories (Unpublished), 2, Box: 5; Box: 6; Box: 7. Janice Daugharty Papers, MS-22. Valdosta State University Archives and Special Collections. Box 5, Folder 17.
Daugharty, Janice. "Sandbury Lock," 1989. 1 electronic record. 1 pdf document. 1 scans.
Keywords: Daugharty, Janice, 1944-; American literature--Women authors; Short stories